(untitled) (Western European Journal of Historical Events and Social Science, 2025)
This article analyzes the life and scholarly-philosophical activities of Shams al-Din Muhammad Tabrizi, one of the prominent representatives of Sufi philosophy. The unique aspects of his life and academic work, as well as his intellectual connections with Jalal al-Din Rumi, are examined based on historical sources.